GERAKAN ECOTON DALAM UPAYA PEMULIHAN SUNGAI BRANTAS - Miatus Sholikhah; Siti Zunariyah (Universitas Sebelas Maret (UNS), 2019)
Most of Indonesia’s rivers fall into the heavily polluted category. One of the heavily polluted rivers in Indonesu is the Brantas River. This research had purpose to understanding the problems in Brantas River and also to know the environmental movement in order to recovering Brantas River. The theory which was used in this research was New Social Movement theory from Rajendra Singh. This research was qualitative research with etnography methods. Data was obtained by observation, detailed interview, and also documentation. The subject of this research was Ecoton, the public accompanied by Ecoton on the headwaters and the downstream of the Brantas River, and the school accompanied by Ecoton. Researcher was using source triangulation techniques to test the collected data legitimation. Researcher used Miles and Huberman’s outlook in data analysis, which consist of three activity lines; data reduction, data presentation and draw conclusions. Results show that there were many problems happened in Brantas River from the headwaters to the downstream. There were five problems found in this research. First, problems in Brantas River headwaters was reclaiming the land functions and illegal logging. Second, there were many abandoned buildings on the riverside. Third, domestic pollution from household. The buildings which were built on the riverside had made the people to easily throw away their garbages to the Brantas River. Mostly it was diapers, which could endanger human and the fishes whom lives in Brantas River. Fourth, the industrial pollution which already exceeds the permittable treshold. Industry had oftenly disposed their waste to the river without conducted the sewage management procedure which then created the new problems in Brantas River: a mass death fish. A mass death fish had become the fifth problems in Brantas River. The damage of environmental condition of Brantas River had pushed the movement from Ecoton. In their movement, Ecoton had the characteristic new social movement which was the ideology of care to the Brantas River damage. The strategy which was used by Ecoton were conducted partitions research, environmental education, advocation and also involved the media on every movement they had done. Ecoton had the non-institutional structure, which was unconcerned with power but put their focus to reach the aims and the visions.